Preparation, Stabilization and Some Properties of Purified Human Plasmin* - Kline, Daniel L; Fishman, Jacob B; With the technical assistance of B. A. Lage (Thrombosis and Haemostasis, 1964)
1. Lysine increased the solubility, decreased the SK requirement and increased the stability of plasmin prepared from purified plasminogen by SK activation.2. A procedure is presented for the rapid and quantitative conversion of plasminogen to plasmin and storage of the plasmin in stable form at neutral pH as a lyophilized powder.3. Approximately 10% for the plasminogen molecule was split off during its activation. No carbohydrate was lost.4. The plasmin isolated was homogeneous in the ultracentrifuge at pH 2.5 and was quantitatively convertible to plasminogen activator by the addition of SK.